Identification of Haplothrips species from Malesia (Thysanoptera, Phlaeothripinae) - Mound, Laurence A. (Zootaxa, 2019)
A key is provided to 13 species of Haplothrips recorded from Malesia, the tropical biogeographic region that extends from Peninsular Malaysia to New Guinea. Three new synonyms are established, and H. aliceae sp.n. is described from Sarawak, Timor-Leste and Thailand. In contrast to recent treatments of Haplothrips, one of the most common members of the genus in Australia, H. angustus Hood is recognised as a syn.n. of H. ganglebaueri Schmutz that is widespread from Iran to Indonesia. Difficulties in distinguishing between three of the most common flower-living, Southeast Asian, species of this genus are discussed: H. anceps Hood from northern Australia, H. chinensis Priesner from Hong Kong, and H. brevitubus (Karny) from Japan.